TLR4 Inactivation in Myeloid Cells Accelerates Bone Healing of a Calvarial Defect Model in Mice. Issue 2 (August 2017) - Wang, Dan; Gilbert, James R.; Taylor, Gwen M.; Sodhi, Chhinder P.; Hackam, David J.; Losee, Joseph E.; Billiar, Timothy R.; Cooper, Gregory M.
Abstract : Background: Toll-like receptor 4 (TLR4) has been implicated in inflammation-induced bone destruction in various chronic bone diseases; however, its direct influence on bone healing is not well understood. The authors' previous study showed accelerated bone healing with higher osteoclastogenesis gene expression in toll-like receptor 4 knockout mice (TLR4 -/- ). This study aimed to further elucidate the underlying cellular mechanisms during fracture healing by generating a myeloid cell-specific toll-like receptor 4 knockout model (Lyz-TLR4 -/- mice). Methods: Calvarial defects, 1.8 mm in diameter, were created in wild-type, TLR4 -/-, and Lyz-TLR4 -/- mice. Bone healing was investigated using micro–computed tomography and histologic, histomorphometric, and immunohistochemistry analyses. Primary bone marrow–derived cells were also isolated from wild-type, TLR4 -/-, and Lyz-TLR4 -/- mice to measure their osteoclast differentiation and resorption properties. Results: A similar faster bone healing response, with active intramembranous bone formation, intense osteopontin staining, and more osteoblast infiltration, was observed in TLR4 -/- and Lyz-TLR4 -/- mice. Tartrate-resistant acid phosphatase staining showed more osteoclast infiltration in Lyz-TLR4 -/- mice than in wild-type mice at day 7. Primary bone marrow–derived cells isolated from TLR4 -/- and Lyz-TLR4 -/- mice presented enhanced osteoclastogenesis and resorption activity compared with those from wild-type mice. Comparable M0, M1, and M2 macrophage infiltration was found among all groups at days 1, 4, and 7. Conclusions: This study revealed that inactivation of toll-like receptor 4 in myeloid cells enhanced osteoclastogenesis and accelerated healing response during skull repair. Together with the role of toll-like receptor 4 in inflammation-mediated bone destruction, it suggests that toll-like receptor 4 might regulate inflammation-induced osteoclastogenesis under different clinical settings. Abstract : Supplemental Digital Content is available in the text.